2020
DOI: 10.7759/cureus.7404
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tuberculous Effects of Statin Therapy: A Review of Literature

Abstract: Tuberculosis (TB) is a chronic infection caused by Mycobacterium tuberculosis (M. TB). It is transmitted through respiratory droplets. Increased cholesterol level is a predisposing factor for TB. M. TB uses cholesterol in the host macrophage membranes to bind and enter the macrophages. Statins are the drugs that are prescribed to hyperlipidemic patients to maintain their lipid levels in the normal range, thereby reducing the risk of stroke and cardiovascular events. Moreover, statins aid in reducing the levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 46 publications
(94 reference statements)
0
17
0
Order By: Relevance
“…Mechanistically, this study proposed that ATRA increases lysosomal acidification via NPC2-mediated reduction in lysosomal cholesterol, thereby promoting Mtb control. Other research has tied ATRA efficacy to autophagy ( 6 ), and targeting cholesterol biosynthesis with statins reduces Mtb growth through an autophagy-dependent mechanism ( 30 , 31 ). These processes may be related, as cholesterol accumulation in macrophages during Mtb infection can interfere with phagolysosomal maturation and autophagic clearance of mycobacteria ( 32 , 33 ).…”
Section: Resultsmentioning
confidence: 99%
“…Mechanistically, this study proposed that ATRA increases lysosomal acidification via NPC2-mediated reduction in lysosomal cholesterol, thereby promoting Mtb control. Other research has tied ATRA efficacy to autophagy ( 6 ), and targeting cholesterol biosynthesis with statins reduces Mtb growth through an autophagy-dependent mechanism ( 30 , 31 ). These processes may be related, as cholesterol accumulation in macrophages during Mtb infection can interfere with phagolysosomal maturation and autophagic clearance of mycobacteria ( 32 , 33 ).…”
Section: Resultsmentioning
confidence: 99%
“…In TB medicine, statins have potential for improving TB treatment outcomes [ 58 ], and are being considered as host-directed therapy in two trials where they are used as adjuvants to TB chemotherapy [ 59 – 61 ]. While not designed to assess the efficacy of statins for CVD prevention in TB patients, dose-safety data from these trials may inform future trials for TB patients with such a goal, similar, perhaps, to the REPRIEVE trial for HIV patients [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…At present, available data regarding the effect of statin administration are minimal in leprosy patients, most only exist in tuberculosis. Tuberculosis infection has several immunopathogenesis similarities with leprae, as they are both caused by mycobacterium species, and current studies on tuberculosis cases present statin as a promising therapeutic agent in two publications by Tahir et al [67] and Alffenaar et al [68]. In vivo studies in mice also showed statin adjuvant in MDT-TB shorten the treatment time and reduce recurrence rates [55], [69].…”
Section: Study Of Pharmacology and Safety Of Statins On Leprosy Mdt Administrationmentioning
confidence: 98%